1995
DOI: 10.1111/j.1600-051x.1995.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and other salivary factors in periodontitis‐affected subjects prior to treatment

Abstract: Salivary calcium was shown to be higher in treated periodontitis-affected subjects (P+) than in periodontitis-free patients (P-). Here the aim was to study whether differences in calcium or other salivary factors exist prior to treatment. The test group consisted of 20 (15 men, 5 women) periodontitis-affected subjects and the control group 15 subjects (10 men, 5 women) free from periodontitis. Paraffin-stimulated whole saliva was collected to determine the flow-rate, calcium and phosphate concentrations, pH, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 12 publications
1
31
1
Order By: Relevance
“…The importance of salivary electrolytes on dental health, especially that of calcium, has been shown earlier (15)(16)(17)(18). An association between increased salivary calcium levels and periodontitis susceptibility has also been found (19,20), and tobacco smoking appears to have an increasing effect on supragingival calculus formation (21).…”
Section: Discussionmentioning
confidence: 92%
“…The importance of salivary electrolytes on dental health, especially that of calcium, has been shown earlier (15)(16)(17)(18). An association between increased salivary calcium levels and periodontitis susceptibility has also been found (19,20), and tobacco smoking appears to have an increasing effect on supragingival calculus formation (21).…”
Section: Discussionmentioning
confidence: 92%
“…As long as natural pH is maintained, the key organisms needed for the dynamic stability stage, such as non-mutans bacteria (mainly non-mutans streptococci and Actinomyces species), are found in high percentages. At this stage, the caries lesions are not formed, and the free calcium concentration around the site is probably close to equilibrium with the concentration in saliva (i.e., 1.2–1.7 mM) [11, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Different bacterial species have shown the ability to grow and form thick biofilms in the presence of naturally occurring levels of exogenous Ca 2+ [12]. Within the human oral cavity, the Ca 2+ concentrations of saliva and gingival crevicular fluid are generally 1.2–1.7 mM [11, 14]. Direct measurement of mineral release from the tooth surface has been applied for in vitro , in situ , and even in vivo samples [15, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Khalil reported a similar finding in his study. (4,5) On the contrary Kamat et al and Sudhir Shetty reported a negative correlation for the same. (6,7) There is very limited research in this field and hence the aim of the present study was To evaluate, if there is any correlation between salivary calcium level and periodontal disease and whether it can be used as a screening tool for periodontal diseases.…”
Section: Introductionmentioning
confidence: 91%